2015
DOI: 10.1055/s-0035-1549319
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Shoulder Instability

Abstract: The glenohumeral joint is an inherently unstable articulation and consequently the most frequently subluxed and frankly dislocated joint in the body. Shoulder instability can be uni- or multidirectional related to acute or repetitive stress and is occasionally secondary to congenital or developmental abnormalities such as a lax joint capsule or glenoid dysplasia. The clinical diagnosis of instability can be difficult, and knowledge of the imaging findings of anterior, posterior, multidirectional, and microinst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 111 publications
(124 reference statements)
0
8
0
Order By: Relevance
“…However, the status of cartilage is not routinely assessed at present, and it is unclear which patients should undergo surgical repair in order to prevent cartilage damage/osteoarthritis. For example, it has been reported that microinstability may lead to many shoulder injuries, including cartilage defects, in overhead athletes 37 , 38 . In these patient groups, T2 mapping may be used to aid therapy decision-making and to identify patient subgroups that would benefit from surgical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the status of cartilage is not routinely assessed at present, and it is unclear which patients should undergo surgical repair in order to prevent cartilage damage/osteoarthritis. For example, it has been reported that microinstability may lead to many shoulder injuries, including cartilage defects, in overhead athletes 37 , 38 . In these patient groups, T2 mapping may be used to aid therapy decision-making and to identify patient subgroups that would benefit from surgical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Shoulder instability is a clinical problem occurring due to tendon laxity, recurrent subluxations or in severe cases complete shoulder dislocation ( Walz, Burge & Steinbach, 2015 ). This is a painful condition, which increases in severity if left untreated.…”
Section: Discussionmentioning
confidence: 99%
“…Thus HS is not a strict requirement for tendon repair and in this respect repair processes in tendon differ from those operative in the repair of skin wounds in perlecan exon 3 null mice. Shoulder instability is a clinical problem occurring due to tendon laxity, recurrent subluxations or in severe cases complete shoulder dislocation (Walz et al 2015). This is a painful condition, which increases in severity if left untreated.…”
Section: Ng2/cspg4 Is Another Transmembrane Proteoglycan Produced By mentioning
confidence: 99%